Irish land bonds: 1891-1938 - Nathan Foley-Fisher; Eoin McLaughlin (The European Association for Banking and Financial History (EABH), 2014)
This paper introduces a new database on Irish land bonds listed on the Dublin Stock Exchange from 1891 to 1938. It outlines the nature of these bonds and presents data on their size, liquidity and market returns. These government-guaranteed bonds arose during a period when the possibility of Irish secession from the United Kingdom appeared ever more likely, and were used to finance the transfer of land ownership from landlords to tenants in Ireland (North and South). Movements in the prices of these bonds can help financial historians understand how financial markets responded to events in the early economic and political history of the Irish Free State, including Irish partition, Independence, Civil War and de facto default. Additionally, understanding these issues has contemporary relevance for regions in Spain (Catalonia, Euskadi), Great Britain (Scotland) and Belgium (Flanders).
Keywords: N23; N24; N53; N54; G15; 330; Irish financial history; land reform; land bonds; Dublin Stock Exchange